The Role of Early Detection by the Intelkam Unit in Addressing Mortal Crimes in the Jurisdiction of the Gresik Police - Tambunan, Hutton Darrel P. (Advances in Police Science Research Journal, 2024)
Motor vehicle theft criminal cases in Gresik Regency are a serious problem because the numberof cases fluctuates. This research describes the role of the Gresik Police Intelligence and SecurityUnit in the crime of theft. Using a qualitative approach and using observation, interviewand document study techniques, the author identifies factors that influence the implementation of early detectioncarried out by the Gresik Police Intelligence and Security Unit. The results of this research showthat early detection carried out by the Gresik Police Intelligence and Security Unit was not optimal. Thisisdue to the small number of DSP members, there are still many members who have not attendedvocational education, and there is still a lack of cooperation and coordination with related agenciesthat can support the implementation of early detection.